(untitled) (Journal Of Educational and Psychological Researches, 2016)
The task of an educational institution Kriyad children need to run the departments possess knowledge management and change the fact that the piece reflects on the educational environment of kindergarten children , which in turn Search has identified targets identification :1- capable knowledge of the directorates of kindergarten.2-alfruq in knowledge management at the directorates of kindergartens depending on the variables of specialization, service and spiritual type .3- administration change from the directorates of kindergarten.4- differences in management changes at the directorates of kindergartens depending on the variables of specialization and the type of service and kindergarten .5- educational environment for children kindergarten .6- differences in the educational environment variable depending on the government kindergarten and my family type .7- the relationship between knowledge management and change management from the directorates of kindergartens and educational environment in kindergarten .To achieve the objectives Find a sample of executives kindergartens were selected in the city of Baghdad was ( 160 ) Directorate were selected ( 300 ) Directorate simple random way , The researcher has built a three Mqaassha first measure of knowledge management to executives Riyadh and the second scale change management to directorates kindergarten and third educational environment scale for kindergarten children . These three scale was presented to a group of experts who are specialists in kindergarten and the measurement and evaluation of educational administration totaling (22) good for the extent of the paragraphs of the meter expires, researcher used two indicators of sincerity are the (virtual honesty and sincerity construction), while the stability of the scale researcher has unearthed each Two types of stability has reached a scale reliability coefficient of the scale of knowledge management in a way re-test (0.77) and the way Alvacrobach (0.80) and reached stability coefficient to measure the management change in a way re-test (0.79), and his ways Alvakr and Bach (0.84) and total coefficient Persistence to gauge the stability of the learning environment in a way observers (0.89), and the way Alvakr and Bach (0.90).In light of the goals of current research and after the application of the scale on the sample research found the following results:1- contrast between managers Riyadh knowledge management variable.2- for Mtgrat relating to the management of knowledge found: But a difference between managers in Riyadh Specialization. B existence of differences depending on the variable of years of service. C There are no differences between managers Riyadh depending on the type of kindergarten.3- There is a difference between Riyadh managers in the management of change.4- in relation to the changes found that there was no difference between the managers accordingly A. There is no difference between managers in Riyadh Specialization B There is no difference between managers Riyadh under the management changes depending on years of service C There are no differences between the managers depending on the type of kindergarten.5- There is a difference in the levels of the educational environment in Riyadh.6- There are no differences in the educational environment depending on the type of government kindergarten, my family7- there relates to the relationship between the three search variables.In light of the search results and the researcher developed a number of recommendations and suggestions , including:1- set up seminars and workshops to explain the concept in the administration to the knowledge and management of changes to directors Riyadh2- conduct a scientific assessment of the Directorates of Education to perform the directors annually to see weaknesses in the management , treatment and encourage good performance there.The researcher presented a set of proposals , including:1- conduct a study on knowledge management and relationship management changes and other changes in the educational environment (such as the Leading director Allaodh characteristics)2- construction of a training program for the development of knowledge management and change management with executives Riyadh